Impact of a 1-day versus 3-day low-residue diet on bowel cleansing quality before colonoscopy: a randomized controlled trial - Gimeno-García, Antonio Z.; de la Barreda Heuser, Raquel; Reygosa, Cristina; Hernandez, Alberto; Mascareño, Isabel; Nicolás-Pérez, David; Jiménez, Alejandro; Lara, Antonio J.; Alarcon-Fernández, Onofre; Hernandez-Guerra, Manuel; Romero, Rafael; Alonso, Inmaculada; González, Yanira; Adrian, Zaida; Hernandez, Goretti; Hernandez, Domingo; Delgado, Rosa; Quintero, Enrique (Endoscopy, 2019)
Background The aim of this study was to assess whether a 3-day low-residue diet (LRD) improved bowel cleansing quality compared with a 1-day LRD regimen.Methods Consecutive patients scheduled for outpatient colonoscopy were randomized to the 1-day LRD or 3-day LRD groups. All patients received a 2-L split-dose of polyethylene glycol plus ascorbic acid. The primary outcome was bowel cleansing quality as evaluated using the Boston Bowel Preparation Scale (BBPS) (adequate cleansing ≥ 2 points per segment). Secondary outcomes were adherence to and level of satisfaction with the LRD, difficulty following the dietary recommendations, and willingness to repeat the same LRD in the future. Intention-to-treat (ITT) and per-protocol (PP) analyses were conducted for the primary outcome. A superiority analysis was performed to demonstrate that a 3-day LRD regimen was superior to a 1-day LRD regimen with a margin of 10 %. Results 390 patients (1-day LRD group = 196, 3-day LRD = 194) were included. The cleansing quality was not significantly different between the groups: ITT analysis 82.7 % (95 % confidence interval [CI] 77.4 to 88.0) vs. 85.6 % (95 %CI 80.7 to 90.5), with odds ratio (OR) 1.2 (95 %CI 0.72 to 2.15); PP analysis 85.0 % (95 %CI 79.9 to 90.1) vs. 88.6 % (95 %CI 84.0 to 93.2), with OR 1.4 (95 %CI 0.88 to 2.52). No differences were found regarding adherence to the diet or cleansing solution, satisfaction or difficulty with the LRD, and the polyp/adenoma detection rates.Conclusion 3-day LRD did not offer advantages over 1-day LRD in preparation for colonoscopy.